Nonoscillatory Solutions of Second-Order Superlinear Dynamic Equations with Integrable Coefficients - Quanwen Lin; Baoguo Jia (Abstract and Applied Analysis)
The asymptotic behavior of nonoscillatory solutions of the superlinear dynamic equation on time scales (𝑟(𝑡)𝑥Δ(𝑡))Δ+𝑝(𝑡)|𝑥(𝜎(𝑡))|𝛾sgn𝑥(𝜎(𝑡))=0, 𝛾>1, is discussed under the condition that 𝑃(𝑡)=lim𝜏→∞∫𝜏𝑡𝑝(𝑠)Δ𝑠 exists and 𝑃(𝑡)≥0 for large 𝑡.